2017
DOI: 10.3390/rs9111115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of External Digital Elevation Model Inaccuracy on StaMPS-PS Processing: A Case Study in Shenzhen, China

Abstract: External Digital Elevation Models (DEMs) with different resolutions and accuracies cause different topographic residuals in differential interferograms of Multi-temporal InSAR (MTInSAR), especially for the phase-based StaMPS-PS. The PS selection and deformation parameter estimation of StaMPS-PS are closely related to the spatially uncorrected error, which is directly affected by external DEMs. However, it is still far from clear how the high resolution and accurate external DEM affects the results of the StaMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…All the others are estimated after unwrapping and then removed before performing unwrapping again. Even though we are using a 30 m SRTM DEM, it has been shown that the influence of DEM on the deformation rate calculation is small and inversely proportional to the wavelength [15]. In Figure 3(c), we observe that the maximum DEM error is observed outside the area of interest reaching~0.01 rad/m, which corresponds to~12 m of DEM error for Envisat.…”
Section: Geofluidsmentioning
confidence: 89%
“…All the others are estimated after unwrapping and then removed before performing unwrapping again. Even though we are using a 30 m SRTM DEM, it has been shown that the influence of DEM on the deformation rate calculation is small and inversely proportional to the wavelength [15]. In Figure 3(c), we observe that the maximum DEM error is observed outside the area of interest reaching~0.01 rad/m, which corresponds to~12 m of DEM error for Envisat.…”
Section: Geofluidsmentioning
confidence: 89%
“…We could improve the PS density even further by using a higher-resolution DEM, if available. Du et al 51 , for instance, have shown that using a 5 m resolution TanDEM-X DEM instead of an SRTM-1arc DEM for X-band SAR data processing using StaMPS has a…”
Section: Discussionmentioning
confidence: 99%
“…Subsidence can also be observed along subways especially when they approaching land reclamation Previous studies of subsidence in Shenzhen mainly use Envisat ASAR images collected between 2006 and 2010 [28][29][30]. Another study used ASAR, ALOS, and TerraSAR-X datasets to investigate the effects of DEM on PS-InSAR in Shenzhen [31]. In this work, apart from using ASAR images acquired between 2004 and 2010, both COSMO-SkyMed images from 2013 to 2016 and Sentinel-1 images from 2015 to 2017 are employed to recover the evolution of Earth surface displacements in Shenzhen.…”
Section: Introductionmentioning
confidence: 99%